2002
DOI: 10.1128/jvi.76.17.8737-8746.2002
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Regulatory Domain on the Carboxyl Terminus of the Measles Virus Nucleocapsid Protein

Abstract: Measles virus (MV) is a negative-strand RNA virus within the Morbillivirus genus of the Paramyxoviridae family. The MV transcriptional complex consists of the virus-encoded RNAdependent RNA polymerase (L), the polymerase cofactor (P), and a ribonucleoprotein template consisting of the singlestranded RNA genome and the nucleocapsid protein (N protein). N protein monomers assemble on the RNA genome during replication to form a single-start left-handed helix, protecting the genome from nuclease degradation. Encap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
112
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(129 citation statements)
references
References 27 publications
13
112
0
1
Order By: Relevance
“…In our report, the HSPA-associated peptides revealed a hydrophobic arrangement, interspersed with hydrophilic residues, including acidic ones, and we did not find preferences for aromatic residues (Table 1). Therefore, our data, with reference to the HSPA binding motif, are in agreement with the in vivo study of Grossmann et al (2004), but are in contrast to HSPA binding motifs which have been proposed in the in vitro studies (Fourie et al 1994;Maeda et al 2007;Takenaka et al 1995;Zhang et al 2002). The binding of the peptides co-purified with HSPA was tested with recombinant HSPA1A and HSPA8 on a peptide array.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In our report, the HSPA-associated peptides revealed a hydrophobic arrangement, interspersed with hydrophilic residues, including acidic ones, and we did not find preferences for aromatic residues (Table 1). Therefore, our data, with reference to the HSPA binding motif, are in agreement with the in vivo study of Grossmann et al (2004), but are in contrast to HSPA binding motifs which have been proposed in the in vitro studies (Fourie et al 1994;Maeda et al 2007;Takenaka et al 1995;Zhang et al 2002). The binding of the peptides co-purified with HSPA was tested with recombinant HSPA1A and HSPA8 on a peptide array.…”
Section: Discussionsupporting
confidence: 75%
“…Therefore, in order to gain further insight into the profile of the HSPA-associated peptides, we studied the preferential binding motif within the peptides. It has been reported that HSPA preferentially binds peptides with a hydrophobic core (Fourie et al 1994;Grossmann et al 2004;Maeda et al 2007;Takenaka et al 1995), with preference for basic (Fourie et al 1994;Grossmann et al 2004;Maeda et al 2007;Takenaka et al 1995) and large aromatic residues (Fourie et al 1994), and that acidic amino acids are rarely present (Fourie et al 1994;Maeda et al 2007;Zhang et al 2002). In our report, the HSPA-associated peptides revealed a hydrophobic arrangement, interspersed with hydrophilic residues, including acidic ones, and we did not find preferences for aromatic residues (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Purification of PNT and of N were carried out as described in (25,48). The 43-kDa N-terminal fragment of N, N CORE , was obtained by limited trypsin digestion of N as described in Ref.…”
Section: Methodsmentioning
confidence: 99%
“…The 43-kDa N-terminal fragment of N, N CORE , was obtained by limited trypsin digestion of N as described in Ref. 25, followed by gel filtration onto a Superdex 200 HR 10/30 column (Amersham Biosciences). N CORE was eluted with 50 mM Tris/HCl, pH 7.5, 1 mM PMSF and stored at Ϫ20°C in the presence of 20% glycerol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation